القراءات الأربع عشرة ةأثرها في تفسير آيات الأحكام دراسة مقاربة بين تفسيري الجصاص وإلكيا الهراسي - Zayd Thabit Abdul Rahman
This research is an applied comparative scientific efforts on the impact of Qira’at in enhancing the interpretation of the verses of judgments in the holy Quran, because this issue involves a difference in elicitation of Islamic judgments. To be noted that the science of Qira’at is honorable because it is deeply related to the Holy Quran,as well as it enriches the Quranic verses with comprehensive meaning. The problem of this study revolves around the fourteen Qira’at and their main role in modulating the religious judgments. The disagreement among the eminent scholars of the doctrines, appeared due to the difference in Qira’at and also the differed in their extrapolation of the rules and judgments. Among those eminent scholars are al-Jassas and al-Kiya al-Harasi who belong to Hanafi and Shafi’I schools respectively. Their tafsirs (interpretation books) are considered two of the most important jurisprudent tafsirs books, which were successful. Each one of them offered his doctrine, accepting its rules and evidence on the problems it encompasses. The research aims to define the concept of the  Qira’at and the scientists’ disagreements to argue about the irregular ones. The research also tried to diagnose the reasons behind the difference in Quranic Qira’at and the heavenly wisdoms in this variation. It also offered a biography for the two scholars al-Jassas and al-Kiya al-Harasi, their methods in interpretation and the reasons behind their disagreements, and extract the influence of Quranic Qira’at in their tafsirs of judgments’ versus. The method adopted in this research is descriptive in general with reliance on inductive, analytical and comparative approaches. These approaches are utilize to discover and discuss opinions and sayings. This research founded; Qira’at are not considered as Quran unless their chain of transmission are accepted by scholars, tafsirs of al-Jassas and al-Kiya al-Harasi are considered as scientific encyclopedias and classified as main sources for Shafi’i and Hanafi schools owing to their efforts of collecting teachings and demonstrated views of their scholars accompanied with their method of weighting between evidence. Their dedication to their sectarianism was a solid platform for their methodology which consequently led to divergent views. The researcher found contradictions in some academic books in the science of Qira’at, the extent of its impact on the legal judgment and discussed it in the light of al-Jassas and al-Kiya al-Harasi instructions. The research recommends any academic editing for the commentaries of al-Jassas and al-Kiya al-Hawasi. Qira’at have a scientific impact interpreting the verses of judgment in the holy Qura’an in the case of plurality which is considered as a variation difference not contradiction. The researcher recommends verifying the two scholars’ tafsirs by attributing Qira’at to their reciters, as far as they do not attribute Qira’at to the scholars, and judge it whether weak or strong.